THE IMPACT OF PRODUCTIVE AND CONSUMPTIVE FINANCINGS ON INDONESIAN ISLAMIC BANKING PROFITABILITY: MARKOV SWITCHING DYNAMIC REGRESSION - Wahid , Wahyu Wibisono; Mawardi, Imron; Al Mustofa, Muhammad Ubaidillah; Risyad, Mohammad Haidar; Nurrohman, Dzikri; Latifah, Nuria (Universitas Airlangga, 2023)
This study investigates the effect of Islamic bank financings on banks' profitability during two distinct periods, namely stable and unstable conditions. This study also examines the profitability tendencies of banks during the two periods mentioned. To answer these objectives, this study applies the Markov Switching Dynamic Regression technique to 173 monthly observations from the Islamic commercial banking industry from December 2007 to March 2022. In stable times, the results indicate that productive financing harms the profitability of Islamic banks. Productive financing entails greater credit risk and can raise principal-agent concerns, moral hazard, and adverse selection. Consequently, productive financing necessitates higher monitoring costs. In an unstable period, consumptive financing negatively affects Islamic bank profitability. The proportion of consumptive financing exceeds the proportion of productive financing. This then increases the risk of credit and default, especially during economic instability when many consumers request reconditioning and even restructuring of financings from the bank. In addition, the results indicate that the profitability of Islamic banking is anticipated to endure longer in stable regimes and to recoup more quickly from unstable or crisis regimes. The findings of this study will likely serve as references and materials for banking management decisions, particularly financing decisions during periods of economic stability and crisis. Islamic banking should prioritize consumer financing during periods of economic stability and increase the proportion of productive financing during periods of economic instability.